Screening of Court Competence Through Dismissal of Process in The General Justice System - Firdaus Arifin (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2024)
In the world there are 2 (two) types of legal systems, namely the Anglo Saxon or Common Law System and the Continental Europe or Civil Law System, Countries with Anglo Saxon legal systems do not recognize the separation of judicial chambers. Indonesia as a continental european adherent in the exercise of judicial power divides into several courts under it, including General Courts, Religious Courts, Administrative Courts, and Military Courts. The number of cases submitted to the District Court as General Court makes the case unfiltered, whether it is under the authority of the District Court or other Courts, in contrast to the State Administrative Court where in its procedural law there is a lawsuit research process that goes to the Court or commonly known as the dismissal process. Therefore, a legal transplant is needed to overcome the problem. In addition, there is a need for a Supreme Court Regulation (PERMA) which regulates the stages of dismissal of proceedings in the General Court in civil cases, commercial cases, industrial relations cases, and cases at the Human Rights Court as well as the revision of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations, the revision of Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes, and the revision of Law Number 26 of 2000 concerning the Human Rights Court.